GTPase Era at the heart of ribosome assembly - Gruffaz, Christelle; Smirnov, Alexandre (Frontiers in Molecular Biosciences, 2023)
Ribosome biogenesis is a key process in all organisms. It relies on coordinated work of multiple proteins and RNAs, including an array of assembly factors. Among them, the GTPase Era stands out as an especially deeply conserved protein, critically required for the assembly of bacterial-type ribosomes from E. coli to humans. In this review, we bring together and critically analyze a wealth of phylogenetic, biochemical, structural, genetic and physiological data about this extensively studied but still insufficiently understood factor. We do so using a comparative and, wherever possible, synthetic approach, by confronting observations from diverse groups of bacteria and eukaryotic organelles (mitochondria and chloroplasts). The emerging consensus posits that Era intervenes relatively early in the small subunit biogenesis and is essential for the proper shaping of the platform which, in its turn, is a prerequisite for efficient translation. The timing of Era action on the ribosome is defined by its interactions with guanosine nucleotides [GTP, GDP, (p)ppGpp], ribosomal RNA, and likely other factors that trigger or delay its GTPase activity. As a critical nexus of the small subunit biogenesis, Era is subject to sophisticated regulatory mechanisms at the transcriptional, post-transcriptional, and post-translational levels. Failure of these mechanisms or a deficiency in Era function entail dramatic generalized consequences for the protein synthesis and far-reaching, pleiotropic effects on the organism physiology, such as the Perrault syndrome in humans.